Features of the territorial structure of investment projects in the Stavropol Territory - Lilia Igorevna Korneva (Наука. Инновации. Технологии, 2022)
We consider the features of the territorial structure of investment projects in the Stavropol Territory, as well as the specifics of the effect of intra-regional factors of attraction and placement of investments in this article. We have collected information that is presented on the official websites of the state authorities of the region, and on their basis have developed own database of data. Geography and industry affiliation of investment projects are compared with the territorial and sectoral structure of the economy that has emerged in the region in this study. We showed that the link between the territorial and sectoral structure of investments, the horizon of their planning, the total amount of funds and the likelihood of implementing investment projects and their placement in the territorial system exists at the intra-regional level. It is proved that investments tend to urban, stable elements of the territorial structure of the economy of the region (industrial centers, nodes and points, federal highways), concentrating labor resources and having high consumer demand and usually correspond to local specialization of the territory.